2010
DOI: 10.1037/a0019815
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal outcomes of young high-risk adolescents with imaginary companions.

Abstract: The creation and cultivation of an imaginary companion is considered to be a healthy form of pretend play in early childhood, but there tends to be a less positive view of older children who have them. To test the extent that having an imaginary companion in middle school is associated with positive or negative outcomes, an ethnically diverse sample of 152 middle school children at high risk for developing problem behaviors were interviewed about imaginary companions, coping styles, and problem behaviors. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 25 publications
3
34
1
3
Order By: Relevance
“…Had it come before, participants might have mentioned their imaginary companions more often. In sum, although we replicated the gender difference often reported in the imaginary companion literature, the current study is not informative with regard to when children are most likely to have an imaginary companion (see Taylor et al, 2004;Taylor, Cartwright, & Carlson, 1993;Taylor et al, 2010).…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Had it come before, participants might have mentioned their imaginary companions more often. In sum, although we replicated the gender difference often reported in the imaginary companion literature, the current study is not informative with regard to when children are most likely to have an imaginary companion (see Taylor et al, 2004;Taylor, Cartwright, & Carlson, 1993;Taylor et al, 2010).…”
Section: Discussioncontrasting
confidence: 43%
“…Notably, a recent study demonstrated that high-risk children who had imaginary companions in middle school, when compared with similar peers who had imaginary companions earlier in childhood or never had them, were significantly more likely to demonstrate positive outcomes following high school (Taylor et al, 2010). Researchers might follow Taylor et al's (2010) lead and further attempt to consider the purpose of pretense in light of the activity's continuation into middle childhood.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous research explored human imagination using diverse approaches, such as philosophical inquiry (Emig, 1983;Warnock, 1976), visual imagery (Gordon, 1949;Richardson, 1969), mental imagery (Marks, 1973(Marks, , 1995, spatial concept (Thurstone & Thurstone, 1965), and imagery companions (Taylor, 1999;Taylor, Hulette, & Dishion, 2010), but few studies have empirically examined imaginative capabilities, let alone developed an evaluation tool for assessing these capabilities. Taking these concerns into account, this study developed the imaginative capability scale (ICS), and then aimed at establishing the reliability, validity, and factor structure of this newly constructed scale.…”
mentioning
confidence: 98%
“…Comforter can be also as imaginary comforter (fantasy). Imaginary comforter as imaginary companion often occurs during childhood [28] to overcome hardship [29].…”
Section: The Stress-comforter Axis and Odd-eccentric Clustermentioning
confidence: 99%